2006
DOI: 10.1890/0012-9658(2006)87[2787:srassi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Species Richness and Stand Stability in Conifer Forests of the Sierra Nevada

Abstract: Theoretical and empirical studies have long suggested that stability and complexity are intimately related, but evidence from long-lived systems at large scales is lacking. Stability can either be driven by complex species interactions, or it can be driven by the presence/absence and abundance of a species best able to perform a specific ecosystem function. We use 64 years of stand productivity measures in forest systems composed of four dominant conifer tree species to contrast the effect of species richness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
80
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 46 publications
8
80
2
1
Order By: Relevance
“…For trees, drought effects have been studied extensively on individual tree species, and has shown that drought decreases growth and increases the sensitivity to insect attacks and diseases, thus increasing the likelihood of tree death (Mattson and Haack 1987). How tree species grown in a mixture react to drought is less clear (DeClerck et al 2006;del Rio et al 2014;Pretzsch et al 2014;Zapater et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For trees, drought effects have been studied extensively on individual tree species, and has shown that drought decreases growth and increases the sensitivity to insect attacks and diseases, thus increasing the likelihood of tree death (Mattson and Haack 1987). How tree species grown in a mixture react to drought is less clear (DeClerck et al 2006;del Rio et al 2014;Pretzsch et al 2014;Zapater et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One important issue in the biodiversity-ecosystem functioning debate is the dependence of ecosystem stability on diversity (Odum 1953;Loreau et al 2002;DeClerck et al 2006). Frequently discussed stability parameters of ecosystems are the resistance to, and the resilience after, disturbances such as drought events or herbivore attack.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that mixed forests show greater resilience with regard to herbivore attack than monospecific stands (Jactel et al 2005;Pretzsch 2005). However, the relationship between tree species diversity and the resistance to, or the resilience after, drought events in forests is not clear yet (Larsen 1995;DeClerck et al 2006). This question is of high relevance to forestry because natural forests are widely being replaced by monospecific plantations in temperate and in tropical regions while the consequences for ecosystem functioning and stability are poorly known.…”
Section: Introductionmentioning
confidence: 99%
“…Plants are 30 to 150 cm tall with globular flower heads (capitula) and commonly, brilliant yellow, orange or red flowers which bloom in July. Each branch will usually have from one to five flower heads containing 15 to 20 seeds per head [4].…”
Section: Introductionmentioning
confidence: 99%
“…Safflower was also known as carthamine in the 19th century [4]. It is a minor crop today, with about 600,000 tons being produced commercially in more than sixty countries worldwide.…”
Section: Introductionmentioning
confidence: 99%